Compósitos cimentícios reforçados com fibras de curauá (Ananas erectifolius) impregnadas com sílica ativa - PINTO, Renata Godinho (Universidade Federal do Pará, 2019)
Vegetal fibers are an alternative for reinforcement in cementitious mortars, unlike the synthetic fibers, they are renewable, biodegradable and low cost. The great limitation of these composites concerns the low durability of the fibers inserted in the cementitious matrix. Therefore, the present research aim to analyze the properties of reinforced mortars with curaua fibers previously impregnated with silica fume. The mix design ratio of the composites was determined with a pilot study. The composites were prepared with mix design ratio 1:3:0.61 and with addition of 2% fibers with 25 mm length. Six families were molded using CP-IV cement and CP-II E. The properties of the composites were verified at 28 days and after natural aging at 180 and 270 days. The characteristics of the curaua fiber used were: density of 1.33 g/cm³, tensile strength of 422.89 MPa and modulus of elasticity of 28.83 GPa. For compressive strength, the composites fibers previous treatment provided a better result than that obtained for mortars with natural fibers. For the tensile strength, inclusion of fibers provided the desired reinforcement improving this property in 45 %. The modulus of elasticity indicated that the addition of the fibers reduced the stiffness of the material. For flexural strength the composite AFCS:IV showed a 57.95 % increase compared to the reference, but it was identified with the natural aging the decrease of the resistance for composites with untreated fibers. The proposed treatment was effective to preserve the toughness of the composites after natural aging. Due to the composites X-ray diffraction, it was verified that the previous treatment of the fibers was effective in limiting the formation of the portlandite in the matrix. This corroborates with micrographs of the mortars, where degradation signals were identified in composites with untreated fibers, while the previously treated fibers remained intact even after natural aging. Thus, it can be considered that the impregnation of the fibers with silica fume improved the properties of the composites and increased the durability of the curaua fibers.